The Influence of Celebrity Endorser, Electronic Word of Mouth, and Halal Label on Purchasing Decisions for Somethinc Products for Muslim Consumers in East Java - Ramadhani, Ulfa Ayu; Suryaningsih, Sri Abidah (Jurnal Iqtisaduna, 2025)
This study aims to analyze the influence of Celebrity endorsers, electronic word of mouth, and Halal Label on the purchasing decision of Somethinc Products on Muslim consumers in East Java. This research method uses a quantitative method with primary data from the distribution of questionnaires online and offline. Sampling using a purposive sampling technique with 200 respondents. The data analysis technique used is Multiple Linear Regression analysis. This study’s results indicate an influence of Celebrity endorsement, electronic word of mouth, and Halal Label on the purchasing decision of Somethinc Products on Muslim consumers in East Java.